Development of Multimedia-Based Speaking Teaching Materials and its Influence on Junior High School Student Motivation - Nazara, Silvia Niat Sari; Ndruru, Mastawati; Telaumbanua, Kalvin Septianus; Waruwu, Rejois (Journal of Computer Science Advancements, 2024)
This research aims to develop multimedia-based speaking teaching materials and test their effect on junior high school students’ learning motivation. The research method used is qualitative research with a descriptive approach. The results of the research show that the use of multimedia-based speaking teaching materials is effective in increasing students’ interest in active participation and learning motivation. Multimedia is considered to be able to make learning more interesting, interactive and fun compared to conventional learning. These findings emphasize the important role of teachers in utilizing multimedia technology to create effective learning and can motivate students in speaking skills. Support from the school and other stakeholders is also needed to facilitate teachers in developing and implementing multimedia-based speaking teaching materials.